2016
DOI: 10.1108/ijchm-07-2014-0360
|View full text |Cite
|
Sign up to set email alerts
|

Work engagement, job satisfaction, and turnover intentions

Abstract: Purpose This study aims to investigate the influence of employee positions (supervisor vs line-level employee) on work-related variables (e.g. work engagement, job satisfaction and turnover intentions). Design/methodology/approach Data were collected from line-level employees and supervisors of 29 mid- to up-scale hotels. A series of one-way ANCOVA were performed to test the position differences in work engagement, job satisfaction and turnover intentions. Hierarchical regression analyses were conducted to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(128 citation statements)
references
References 88 publications
7
113
0
8
Order By: Relevance
“…These findings correlate with engagement findings from studies in other work environments and studies of medical residents that associated job satisfaction positively with work engagement. 10,11,31,32 Overall, employees are more engaged when they work in an environment that provides practical and psychologically meaningful support as well as advancement and promotion opportunities. 33 To be effective, support, development and advancement opportunities must be clearly communicated to FMR managers.…”
Section: Discussionmentioning
confidence: 99%
“…These findings correlate with engagement findings from studies in other work environments and studies of medical residents that associated job satisfaction positively with work engagement. 10,11,31,32 Overall, employees are more engaged when they work in an environment that provides practical and psychologically meaningful support as well as advancement and promotion opportunities. 33 To be effective, support, development and advancement opportunities must be clearly communicated to FMR managers.…”
Section: Discussionmentioning
confidence: 99%
“…Customer satisfaction and customer loyalty are the most significant determinants for PSS success since retaining existing customers is less costly than acquiring new ones [118,226]. Given the complexity of the PSS value proposition, satisfied and loyal customers are also critical to further promote consumer acceptance through word-of-mouth behavior [226][227][228]. Customer satisfaction occurs through a process of value co-creation between customers and employees of the PSS provider.…”
Section: Employee Commitmentmentioning
confidence: 99%
“…Therefore, findings are susceptible to respondents' socioeconomic class (e.g., prestige and status) and career needs. Previous research has shown that supervisors and line-level employees exhibit difference in work engagement and intentions to quit (Lu, Lu, Gursoy, & Neale, 2016). Future research may consider the role of job position and examine incentive travelers who are at the managerial or executive level within an organization.…”
Section: Limations and Future Researchmentioning
confidence: 99%